Meta Analysis of Yoga Benefits for Individuals with Visual Impairment and Disabilities Using Python - Himanshu Parihar; Atharva mithbawka; Arvind Choudhary; Prof. Dr. Shubhalaxmi Joshi (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The synchronization of Yoga with those of the differently abled remains an unexplored region for which specific studies must be conducted. By collecting data and studying various patterns of multiple groups with different disabilities as well as visual impairments, a prominent format can be established by which these groups can be benefitted. By collecting raw data this research aims at extracting and providing lucrative results by which Yoga can help people with disabilities as well as introduce them with various health advantages which may help improve their quality of life.